Transcultural Hamlet Representations of Ophelia and Gertrud in 21st-century Iran - Robabeh Jalayer; Alireza Anushiravani (The English Department, Faculty of Humanities & Creative Industries, Petra Christian University, 2017)
Multitudes of intermedial Shakespearean adaptations have captured Iranian theatrical stage, cinema or radio as the Bard’s texts are frequently modernized, transfigured and indigenized especially since 1975. Hamlet works well in the mechanisms of temporality, spatiality, power, control and sexuality, socio-political discourses, economic upheaval, female self and gender struggles even in the twentieth and twenty-first centuries. Hence, Iranian directors such as Varuzh Karim-Masihi and Arash Dadgar as well as the British director Gregory Doran have re-interpreted this text based on new ideological grounds in which the characters are at times similar or different. In this article, the transformation and characterization of major characters, especially female ones such as Gertrud/Mah-Tal’at and Ophelia/Mahtab, are analyzed based on Hutcheon’s Adaptation Theory and Foucault's surveillance to see how they are represented in an Asian society whose Islamic ideology necessitates a unique transcultural, transhistorical rendition. The comparative study of these works reveals that since Shakespeare’s era, women's social representations have gone under great changes although the governments' surveillance has largely increased.